Discovery of Small Molecule NSC290956 as a Therapeutic Agent for KRas Mutant Non-Small-Cell Lung Cancer - Jiaxin Zhang; Jiaxin Zhang; Zuojia Liu; Wenjing Zhao; Xunzhe Yin; Xiliang Zheng; Chuanbo Liu; Jin Wang; Erkang Wang; Erkang Wang (Frontiers Media S.A., 2022)
HRas-GTP has a transient intermediate state with a "non-signaling open conformation" in GTP hydrolysis and nucleotide exchange. Due to the same hydrolysis process and the structural homology, it can be speculated that the active KRas adopts the same characteristics with the "open conformation." This implies that agents locking this "open conformation" may theoretically block KRas-dependent signaling. Applying our specificity-affinity drug screening approach, NSC290956 was chosen by high affinity and specificity interaction with the "open conformation" structure HRasG60A-GppNp. In mutant KRas-driven non-small-cell lung cancer (NSCLC) model system, NSC290956 effectively suppresses the KRas-GTP state and gives pharmacological KRas inhibition with concomitant blockages of both the MAPK-ERK and AKT-mTOR pathways. The dual inhibitory effects lead to the metabolic phenotype switching from glycolysis to mitochondrial metabolism, which promotes the cancer cell death. In the xenograft model, NSC290956 significantly reduces H358 tumor growth in nude mice by mechanisms similar to those observed in the cells. Our work indicates that NSC290956 can be a promising agent for the mutant KRas-driven NSCLC therapy.